2013
DOI: 10.1371/journal.pone.0080711
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Antenatal Common Mental Disorders in Low-Obstetric Risk Women and Adverse Birth Outcomes in Their Offspring: Results from the CDS Study in Ghana and Côte D'Ivoire

Abstract: BackgroundEvidence linking common mental disorders (CMD) in pregnant women to adverse birth outcomes is inconsistent, and studies often failed to control for pregnancy complications. This study aimed to explore the association between antenatal depression and anxiety symptoms and birth outcomes in a low-obstetric risk sample of mother/child dyads in Ghana and Côte d’Ivoire.MethodsIn 2010-2011, a prospective cohort of 1030 women in their third trimester in Ghana and Côte d’Ivoire was enrolled. Depression and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…Third trimester Aaron et al (2015) 46 Bjork et al (2015) 47 Cheng et al (2015) 48 Dubber et al (2015) 49 Ibanex et al (2015) 50 Pazzagl et al (2015) 51 Pisoni et al (2016) 52 Vilela et al (2015) 37 Broekman et al (2014) 13 Ferreira et al (2014) 53 Garthus-Niegel et al (2014) 3 Huizink et al (2014) 29 Meijer et al (2014) 30 Jokic-Bergic et al (2014) 54 Tan et al (2014) 55 Verreault et al (2014) 56 Bindt et al (2013) 57 George et al (2013) 7 Makara-Studzinska et al (2013) 31 Roos et al (2013) 40 Figueiredo & Conde (2011) 32 Mohammad et al (2011) 58 Hall et al (2009) 5 DiPietro et al (2008) 59 Keeton et al (2008) 60 Lee et al (2007) 34 Shi et al (2007) 43 Bene et al (2005) 12 Heron et al (2004) 44 Rondo et al (2003) 35 Ross et al (2003) 61 Teixeira et al (1999) 62 Crandon et al (1979) 63 Subtotal (I 2 = 99%, P = 0.000) 2 and online Fig. DS1).…”
Section: Second Trimestermentioning
confidence: 99%
“…Third trimester Aaron et al (2015) 46 Bjork et al (2015) 47 Cheng et al (2015) 48 Dubber et al (2015) 49 Ibanex et al (2015) 50 Pazzagl et al (2015) 51 Pisoni et al (2016) 52 Vilela et al (2015) 37 Broekman et al (2014) 13 Ferreira et al (2014) 53 Garthus-Niegel et al (2014) 3 Huizink et al (2014) 29 Meijer et al (2014) 30 Jokic-Bergic et al (2014) 54 Tan et al (2014) 55 Verreault et al (2014) 56 Bindt et al (2013) 57 George et al (2013) 7 Makara-Studzinska et al (2013) 31 Roos et al (2013) 40 Figueiredo & Conde (2011) 32 Mohammad et al (2011) 58 Hall et al (2009) 5 DiPietro et al (2008) 59 Keeton et al (2008) 60 Lee et al (2007) 34 Shi et al (2007) 43 Bene et al (2005) 12 Heron et al (2004) 44 Rondo et al (2003) 35 Ross et al (2003) 61 Teixeira et al (1999) 62 Crandon et al (1979) 63 Subtotal (I 2 = 99%, P = 0.000) 2 and online Fig. DS1).…”
Section: Second Trimestermentioning
confidence: 99%
“…The same study revealed that pregnant women described episodes of bleeding during the 1 st and 2 nd trimesters of pregnancy, which were associated with signs and symptoms that indicated depression and anxiety. 8 Results from a study performed with pregnant adolescents showed an association between depression and episodes of bleeding. Adolescents who had this complication were 6.7 times more likely to have depression, 17 evidence that corroborates the results expected for this study.…”
Section: Common Mental Disorders In Pregnant Womenmentioning
confidence: 99%
“…3,6,7 The following factors are also associated: living without a partner, planned pregnancy, gestational age and gestational complications. 3,5,6,8 Thus, the present study is justified when the probability of CMD in this special time women experience and the variables that increase its chances during pregnancy are taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…During the same time period, an equal number of controls were randomly selected from all women with births of at least 37 completed weeks of gestation and birth weight of at least 2500 g from the same regions as the cases. The cases and controls were required to meet the following criteria: (1) the mothers were to have lived in one of the seven innercity districts of Wuhan for at least 2 years, (2) to have given birth in a hospital located in the inner-city and rested in the inner city following delivery, (3) to not have a history of mental disorder prior to pregnancy, (4) and to deliver an infant with a gestational age between 20 and 46 weeks, (5) and a birth weight between 500 and 5000 g, and (6) to have a singleton live birth without any birth defects. 4308 cases and 4308 controls were included in this study.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Because of differences in study populations, socioeconomic background, and maternal health profile, evidence on the effect of CMDP on PTB is somewhat conflicting. A recent meta-analysis suggested that CMDP were associated with an increased risk of PTB [13], but individual studies done in low-obstetric risk women failed to observe such an association [3]. These results demonstrated the importance of studying the cultural context related to the association between mental health and birth outcomes.…”
Section: Introductionmentioning
confidence: 97%